A computer simulation model for analysing performance of inventory policy in multi-product mode in two-echelon supply chain. Issue 1 (9th December 2010) - Azadeh, Ali; Allahverdiloo, M.; Shirkouhi, Salman Nazari
In this paper, a simulation model is presented for analysing performance of inventory policy in multi-product mode in two-echelon supply chain including four retailers and one capacitated supplier. The inventory policies include: Economic Order Quantity (EOQ), Periodic Order Quantity (POQ), Silver-Meal (SM), and Part-Period Balancing (PPB). The results also show that sharing planned order information (OIS) is better than sharing only demand information (DIS), which, in turn, is better than No Information Sharing (NIS), for all inventory policies used by the retailers.